Relationship between Sustainable Development and Health: The Case of Turkey - Kanberoglu, Zafer; Günsan, Nida (International Journal of Contemporary Economics and Administrative Sciences, 2018)
Sustainable development is the fulfillment of the needs of the present generation without destroying the ability of future generations to meet their own needs.Among the main elements of sustainable development,there are economic elements, socio-cultural elements and environmental elements.Reducing world hunger, gender equality, clean water and sanitary conditions, appropriate work and economic growth, industry-innovation and infrastructure, reduction of inequalities, responsible consumption and production, aquatic life, terrestrial life, peace and justice, poverty reduction, accessible clean energy, sustainable cities and habitats and healthy individuals are some of the key objectives of sustainable development. Health is considered one of the important indicators in achieving these goals. Health is one of the basic needs of mankind.According to the definition made by the World Health Organization health; is expressed as the state of full well-being of the individuals in physical, spiritual and social aspects. It is natural that this state of full well-being is closely related to the economic development and the environment it affects.In evaluating the goals of sustainable development; health indicators which is used include variables such as nutrition status, mortality, hygiene conditions, drinking water, and health services. Relationship between sustainable development and health will be examined within Turkey example study.